A communication-enhanced price-based control scheme for HVAC systems - Fernandez, E.; Jamborsalamati, P.; Hossain, M.J.; Amin, Uzma (2017)
Real-time electricity pricing has been a key issue in Australia's national electricity markets. The average electricity bill paid by a consumer is influenced by the amount of energy consumption by different loads and their time of use. Certain loads such as dishwashers and pool pumps are deferrable while loads such as lighting and refrigeration are non-deferable. HVAC (heating, ventilation and air conditioning) systems contribute to a major part of the energy consumption of a building. This paper discusses the design of real-time energy pricing in a transactive environment where the key players will be the consumers. The designed real-time control scheme in this paper is to define the final thermostat set-point for each HVAC based on the bidding price. In addition, this paper proposes the communication architecture to implement the designed control scheme through two-way communication between HVACs, data aggregator and the central controller. The proposed architecture utilizes the Message Queue Telemetry Transport (MQTT) protocol which is the state-of-the-art lightweight messaging protocol for use on top of the TCP/IP protocol. From the analysis, it is evident that the proposed algorithm enables customers to reduce energy costs and increases energy efficiency.